2022
DOI: 10.3389/fcimb.2022.856633
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Protected Against pseudomonas aeruginosa Pneumonia via Restoring Treg/Th17 Balance and Metabolism

Abstract: Backgrounds and PurposeThe theory of “entero-pulmonary axis” proves that pneumonia leads to gut microbiota disturbance and Treg/Th17 immune imbalance. This study is aimed to explore the potential mechanism of fecal microbiota transplantation (FMT) in the treatment of Pseudomonas aeruginosa pneumonia, in order to provide new insights into the treatment of pneumonia.MethodsPseudomonas aeruginosa and C57/BL6 mice were used to construct the acute pneumonia mouse model, and FMT was treated. Histopathological change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…The Treg cells (isolated from the rat spleen) were added to identify with CD4 (11‐0043‐82), CD25 (25‐0251‐82), and Foxp3 (35‐5773‐82) antibodies. [ 38 ] The antibodies were purchased from eBiosciences (USA). Cells and antibodies were incubated in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…The Treg cells (isolated from the rat spleen) were added to identify with CD4 (11‐0043‐82), CD25 (25‐0251‐82), and Foxp3 (35‐5773‐82) antibodies. [ 38 ] The antibodies were purchased from eBiosciences (USA). Cells and antibodies were incubated in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Xuan Bai Cheng Qi decoction acts on the Foxp3/RORyt signaling pathway, modulating Treg and Th17 cell-mediated pulmonary-intestinal immune imbalance [9]. Fecal microbiota transplantation (FMT) in Pseudomonas aeruginosa-infected mice restores intestinal microbial abundance and diversity, suppresses inflammation and tissue damage, and improves Treg/Th17 cell immune balance [10]. Following antibiotic treatment during pregnancy, neonatal mice inoculated with bacillus Calmette-Guérin did not show alterations in the number of TB10.4 T cell epitopes, suggesting that maternal antibiotic use during pregnancy may contribute to the development of immune defects and alter offspring susceptibility to Mycobacterium tuberculosis [11].…”
Section: Infectious Diseases Of the Lungsmentioning
confidence: 99%
“…The role of commensal microorganisms in regulating the balance of pro-inflammatory and anti-inflammatory cells is also an important topic. The "gut-lung axis" theory demonstrated that pneumonia could lead to intestinal bacterial dysbiosis and Th17/Regulatory T cells (Treg) cells immune imbalance [ 44 ]. Both Th17 and Treg are differentiated from the naïve CD4 T cell [ 45 ], and are most abundant on the mucosal surface, especially in the intestinal lamina propria.…”
Section: Immune Crosstalk In the Gut-lung Axismentioning
confidence: 99%